2013
DOI: 10.5551/jat.15263
|View full text |Cite
|
Sign up to set email alerts
|

Probucol Suppresses Initiation of Chronic Hemodialysis Therapy and Renal Dysfunction-Related Death in Diabetic Nephropathy Patients: Sakura Study

Abstract: Aim: Probucol has antioxidant as well as cholesterol-lowering effects. We examined the effect of probucol on the progression of diabetic nephropathy. We named this study 'Sakura Study' after our hospital and city. Methods: We performed a randomized, open trial on 162 type 2 diabetic patients with clinical albuminuria (urinary albumin excretion >300 mg/g creatinine). Eighty patients were assigned to probucol treatment (500 mg/day) and 82 patients to no probucol treatment. All patients were followed for five yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
3
13
1
Order By: Relevance
“…10,11 However, a significant additional LDL-C-lowering effect of probucol was observed in this study. As probucol upregulates the fractional catabolic rate of LDL-C via an LDL receptor-independent pathway and increasing bile acid synthesis, 18,19 its effect on LDL-C lowering might be complementary to that of statins.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…10,11 However, a significant additional LDL-C-lowering effect of probucol was observed in this study. As probucol upregulates the fractional catabolic rate of LDL-C via an LDL receptor-independent pathway and increasing bile acid synthesis, 18,19 its effect on LDL-C lowering might be complementary to that of statins.…”
Section: Discussioncontrasting
confidence: 44%
“…Although lower levels of total and LDL-C were achieved in subjects allocated to the probucol 250 and 500 mg/d groups, there The results of this multicenter, double-blind, placebo-controlled study are in contrast with previous open-label studies in which probucol suppressed the progression of proteinuria and decline in renal function. 10,11 In addition to the open-label study design of the previous studies, the different proportions of subjects who used ACEIs/ARBs could explain the discrepancy. In a previous study, 17.6% of subjects in probucol group and 21.6% in the control group used ACEIs/ARBs, 10 and a significant reduction in urinary protein excretion in the probucol group was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study revealed that treatment with vildagliptin + telmisartan controlled blood pressure, renovascular structural and biochemical parameters in diabetic neuropathy rats (4). Endo et al (8) performed a randomized, open trial on 162 type 2 diabetic patients and found that probucol suppressed the progression of DN and renal dysfunction events.…”
Section: Introductionmentioning
confidence: 99%